Healthcare resource utilization burden associated with cognitive impairments identified through natural language processing among patients with schizophrenia in the United States - Jerome Vaccaro; Mona Nili; Pin Xiang; James K. Nelson; Cory Pack; Randall Thompson; Joe Vasey; Joseph Parks (Schizophrenia)
Abstract While cognitive impairments in schizophrenia are well documented in research, their identification and impact in clinical practice remain less well understood, despite their association with high patient burden and impact on long-term functional outcomes. In this study we aimed to identify documented cognitive impairments using natural language processing (NLP) and to characterize treatment patterns and healthcare resource utilization (HCRU) among patients with schizophrenia. This US retrospective cohort study used electronic health records (EHR) linked to administrative claims data from January 2016 through February 2023. Adult patients (≥18 years) with at least two schizophrenia diagnosis codes were included. Cognitive impairments were identified by NLP. Patient characteristics were assessed in the 12 months preceding the index date (first documented schizophrenia diagnosis). Treatment patterns and HCRU were measured over the 12 months after index date. A total of 79,326 patients were enrolled in the EHR cohort and 19,974 (25.2%) had documented cognitive impairments. Impairments in “Reasoning and Problem Solving” were identified most often (70.4%) followed by “Working Memory” (27.1%) and “Attention and Vigilance” (19.2%). In the EHR cohort, 11,293 patients (14.2%) had linked claims. Patients with documented cognitive impairments had more HCRU including outpatient visits, psychosocial interventions, and all-cause healthcare claims than patients without documented cognitive impairments (all p < 0.001). Patients with cognitive impairments had greater psychiatric pharmacy utilization than those without cognitive impairments. These observational data add to the limited published literature on cognitive impairments in patients with schizophrenia in the US. The low documented identification of cognitive impairments in this study underscores the importance of improving recognition and documentation of this important domain of schizophrenia. The association of cognitive impairments with high healthcare utilization further emphasizes the need for better treatment options for patients with schizophrenia.